Tectonic Inversion of the Abanico Basin Eastern Border and the Structuring of the Aconcagua Thrust-Fold Belt, Southern Central Andes at 32°-33°S - Jara-Munoz, P (Elsevier Ltd, 2023)
Previous geologic studies and structural interpretations of the Meso-Cenozoic units in the Andean Principal Cordillera, between 32°- 33°S, have faced many difficulties due to the strong variability in volcanic deposits thickness, the structural complexity that affects the involved units, and the scarcity of geochronological data that prevents defining a clear boundary between them. Structural-lithologic work carried out between 32°45′-33°S allowed us to recognize and define 4 different lithologic units along the Aconcagua-Juncal river valleys: one marine sedimentary unit assigned to the Cretaceous Mendoza Group and Late Jurassic exposures from the Río Damas/Tordillo Formation, and 3 volcano-sedimentary units mainly associated with Cenozoic volcanism represented by the Farellones, Abanico, and Cristo Redentor formations. The stratigraphic-structural model proposed in this work also allows for defining 3 structural domains throughout the study area: a western domain close to the Pocuro Fault Zone, a central domain, and an eastern domain close to the Alto del Juncal Fault Zone, next to the Chile-Argentina international border. The western and central domains show folds with larger wavelengths than the eastern domain, while the eastern domain shows intense deformation related to the emplacement and evolution of the Aconcagua fold and thrust belt. This deformation results from tectonic events which mainly occurred between the Upper Oligocene and Miocene. In the study region, these events caused a minimum shortening of ∼30 km in the Principal Cordillera. Based on the collected information, the Alto del Juncal Fault is also interpreted as the eastern Abanico basin bounding fault in which the Aconcagua fold-thrust belt is rooted. © 2023 Elsevier Ltd
Keywords: Andes; Central Chile Principal cordillera; Aconcagua fold-thrust belt; Abanico basin; Tectonic inversion